A 20-year follow-up of men aged 55-64 including coal-miners and foundry workers in Staveley, Derbyshire. Issue 3 (August 1980) - Cochrane, A L; Moore, F
Abstract : A survey carried out in 1957 by the Medical Research Council's Pneumoconiosis Unit was based on a private census, with brief industrial histories of men aged 55-64 and 25-34. Four groups were established in this way–"non-dusty, " "pure coal-mining, " "pure foundry, " and "other and mixed." In the 55-64 age group all 387 men have been followed up except for one man, about whom we have no information, and another man, for whom we know the date of death but not the certified cause. The mortality from all causes is similar in all four groups, but there is a slight suggestion of a past or present dust problem, or both, in the foundry population. It is suggested that Staveley is, so far, the bet area we have found for studying simple pneumoconiosis of coal-miners. If this suggestion is accepted the mortality rates for miners and ex-miners with simple pneumoconiosis seem similar to those of the same age not exposed to industrial dusts, living in the same area, with similar smoking habits.